Analisis Ekonomi Politik Marxian dalam Pertumbuhan Ekonomi di Indonesia - Alin Nursipa; Eli Apud Saepudin; Alya Mutiara Alya Mutiara; Anita Maulina; Sri Hasanah; Sabila Nur Afnia (UNIVERSITAS SERAMBI MEKKAH, 2024)
This research aims to analyze the development and application of Marxian political economy in Indonesia. Economic Marxism is a perspective based on the thought of Karl Marx and criticizes capitalism as an exploitative economic system. In the Indonesian context, Marxian economics has a long history related to the struggle against colonialism and efforts to build a more just economic system. This research uses a qualitative approach by conducting a literature study of related sources such as books, journals, and historical documents. The analysis is conducted by tracing the development of the Marxist movement in Indonesia, its influence on economic policy, as well as the challenges and criticisms faced in its implementation The results show that Marxian economics in Indonesia had a significant influence in the formation of ideology and resistance movements against colonialism. However, after independence, the application of Marxian economics faced major challenges due to ideological competition and political pressure. Nonetheless, some Marxian economic principles such as social justice and wealth equality still influence economic policy in Indonesia..